Managerial Skills for Managing Construction Safety - Riza Yosia Sunindijo; Patrick X.W. Zou; Andrew Dainty (Civil Engineering Dimension, 2017)
Previous research has suggested that self-awareness, visioning, and sincerity are foundational managerial skills for delivering positive safety outcomes in construction projects. This paper aims to verify this finding and to suggest learning approaches for developing these skills in practice. Interviews with experienced construction practitioners were analysed thematically to find common themes. The thematic analysis confirms the necessity of the managerial skills identified in the previous research for managing construction safety and provides directions for construction organisations to improve safety learning. Existing approaches, which mainly adopt the cognitivism learning philosophy, may not be sufficient because the nature of learning in practice aligns with social constructivism, showing that learning occurs informally through interactions with people and artefacts at work instead of in a classroom-structured environment. Furthermore, although learning methods to develop safety skills have been suggested, there remains a need for better statistical evidence of the effectiveness of these methods in delivering safety outcomes.